Use of non-pharmacological methods in managing labour pain: experiences of nurse-midwives in two selected district hospitals in eastern Tanzania - Dorkasi L. Mwakawanga; Lilian T. Mselle; Victor Z. Chikwala; Nathanael Sirili (BMC, 2022)
Abstract Background Labour pain usually brings with it many concerns for a parturient and her family. The majority of the women in labour pain may require some sort of pain relief method during this period, be it pharmacological or non-pharmacological. In Tanzania, the use of non-pharmacological methods to relief labour pain remains low among nurse-midwives. We analysed the experiences of nurse-midwives in the use of non-pharmacological methods to manage labour pain, in two selected districts of Pwani and Dar es Salaam regions in eastern Tanzania. This paper describes Non-pharmacological Methods (NPMs) currently used by nurse-midwives, the facilitators, myths and fears related to the use of NPMs. Materials and Methods An exploratory qualitative study using in-depth interviews was conducted with 18 purposively recruited nurse-midwives working in labour wards in two selected district hospitals in Pwani and Dar es Salaam regions in eastern Tanzania. Qualitative conventional content analysis was used to generate categories describing the experience of using non-pharmacological methods in managing labour pain. Results This study revealed that nurse-midwives encouraged women to tolerate labour pain and instructed them to change positions and to do deep breathing exercises as a means to relief labour pain. Nurse-midwives' inner motives facilitated the use of non-pharmacological strategies for labour pain relief despite the fear of using them and myths that labour pain is necessary for childbirth. Conclusion This study generates information about the use of non-pharmacological strategies to relief labour pain. Although nurse-midwives are motivated to apply various non-pharmacological strategies to relief labour pain, fear and misconceptions about the necessity of labour pain during childbirth prohibit the effective use of these strategies. Therefore, together with capacity building the nurse-midwives in the use of non-pharmacological strategies to relief labour pain, efforts should be made to address the misconceptions that may partly be of socio-cultural origin.